2000
DOI: 10.1093/humrep/15.6.1256
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor α concentrations in the peritoneal fluid of infertile women with minimal or mild endometriosis are lower in patients with red lesions only than in patients without red lesions

Abstract: Tumour necrosis factor alpha (TNFalpha) of peritoneal fluid is believed to have important pro-inflammatory and angiogenic activities in the complex mechanisms of development of peritoneal endometriotic lesions. We have evaluated the concentrations of TNFalpha and macrophages in peritoneal fluid of infertile women with minimal or mild endometriosis and related them to the presence of peritoneal red lesions alone (red lesions only group; n = 11) or their absence (non-red lesions group; n = 36). A group of 39 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 32 publications
2
25
0
1
Order By: Relevance
“…We chose to study PDGF, VEGF, IL‐6, RANTES, IL1‐β, IL‐8, TNF‐α, MCP‐1, sFas, and sFasL, as they have been implicated in the possible pathogenesis of endometriosis. In agreement with other studies, we have found a significantly higher concentration of IL‐8, 5,6,12 IL‐6 14,15 and MCP‐1 16–18 in the PF of women with active endometriosis. However, we did not find an equivalent increase in the concentration of these cytokines in the serum of these women, compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We chose to study PDGF, VEGF, IL‐6, RANTES, IL1‐β, IL‐8, TNF‐α, MCP‐1, sFas, and sFasL, as they have been implicated in the possible pathogenesis of endometriosis. In agreement with other studies, we have found a significantly higher concentration of IL‐8, 5,6,12 IL‐6 14,15 and MCP‐1 16–18 in the PF of women with active endometriosis. However, we did not find an equivalent increase in the concentration of these cytokines in the serum of these women, compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…The dynamic interplay among cytokines may contribute in the creation of a microenvironment which favors the implantation of endometrial cells and the progression of the disease. Numerous authors have studied the presence and role of various cytokines in the serum and PF of women with endometriosis 5–10 . Available data in the literature however, have not been consistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iwabe et al [13] demonstrated that TNF-␣ stimulates proliferation of endometriotic stromal cells through induction of IL-8 gene and protein expression and concluded, that TNF-␣ may be one of the essential factors for the pathogenesis of endometriosis. It has been shown [12,35] , that in women with endometriosis, peritoneal fl uid TNF-␣ concentrations correlate with the stage of the disease. Additionally, several studies reported signifi cantly higher TNF-␣ serum levels in patients with endometriosis compared to the control group, especially in early stages of the disease pointing out an involvement and a role played by acute infl ammatory processes at these early stages [15,36] .…”
Section: Regulated Upon Activation Normal T Cells Expressed and Secrmentioning
confidence: 99%
“…Several studies have suggested that the immune system plays a pivotal role in the pathogenesis and progression of this disease in humans [2][3][4][5] . Although many authors have described a correlation between the endometriosis-associated inflammatory response and peritoneal fluid macrophage-dependent secretion of interleukin (IL)-1, IL-2, IL-6, IL-8, IL-10 and tumor necrosis factor (TNF) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] , the characteristics of peritoneal fluid mononuclear cell patterns and the types of lymphokine primarily involved in the pathogenesis of endometriosis remain controversial 25 .…”
Section: Introductionmentioning
confidence: 99%